Protagonismo laico em tempos de hipermodernidade: desafios para uma teologia prática do laicato - Fiore, André Gustavo Di (2023)
The French philosopher Gilles Lipovetsky, when defining contemporary society from its traits and behaviors, develops the category of hypermodernity, which has as premise the rapid social transformations in the field of ethics, making individualism and a posture based on painless ethics be a mark of the contemporary individual, subject of himself, but intoxicated by a social relationship influenced by fashion and consumption. In harmonious dialogue with Lipovetsky's position, numerous ecclesial documents, such as several conciliar texts and most documents from Latin American episcopal conferences, also portray sudden social changes, individualism and influences on the individual as social and ecclesiastical. Based on this context, the research problem developed from now on, focused on the question of the hypermodern laity and the reasons why the theoretical proposals of a lay missionary discipleship from its baptismal role, present in ecclesial documents since the Second Vatican Council, find it difficult to cross the barrier between theory and practice. In this sense, this work, developed from a deductive analysis and structured from the principles of the see, judge and act method, had the general objective of reflecting on the effects of lay behavior in pastoral praxis in the light of the category of hypermodernity, extending such reflections, more specifically, for the understanding of identity and social behavior, for a critical analysis of the hypermodern layperson, and finally for a proposal of a theology and pastoral praxis capable of promoting a lay missionary discipleship coherent with the evangelical and ecclesial intentions